K / molecular sieve type aldol condensation catalyst and preparation method thereof

By combining alkali metal potassium with zeolite molecular sieve, a catalyst is prepared for catalyzing the aldol condensation reaction between methyl acetate and formaldehyde, which solves the problems of high and scarcity of catalysts in the prior art, and achieves a high-efficiency and low-cost catalytic effect.

CN119633889AInactive Publication Date: 2025-03-18INSTITUTE OF PROCESS ENGINEERING CHINESE ACADEMY OF SCIENCES +1
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202411816076.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-11
Publication Date
2025-03-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, the aldol condensation catalyst of methyl acetate and formaldehyde is costly and scarce, making it difficult to widely use in industrial applications.

Method used

By combining alkali metal potassium as an active component with the zeolite molecular sieve support, a metal-modified molecular sieve catalyst was prepared to catalyze aldol condensation reaction between methyl acetate and formaldehyde, achieving an effective replacement of conventional cesium-based catalysts.

Benefits of technology

This catalyst significantly improves the efficiency of the reaction and product selectivity, reduces the preparation cost of the catalyst, and realizes the replacement of alkali metal K on Cs, with good industrial application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005181827210000101
    Figure BDA0005181827210000101
  • Figure BDA0005181827210000111
    Figure BDA0005181827210000111
Patent Text Reader

Abstract

The invention discloses a K / molecular sieve type catalyst capable of efficiently catalyzing aldol condensation reaction and a preparation method thereof. According to the catalyst, cheap alkali metal potassium is used as an active component, a specific microporous molecular sieve is used as a carrier, and aldol condensation reaction can be catalyzed in a high-activity and high-selectivity manner through fine regulation and control of acid-base site distribution on the surface of the catalyst, so that the target product methyl acrylate is generated. According to the catalyst, cheap alkali metal K is taken as an active component, and the advantages of shape selectivity and large specific surface area of the molecular sieve are combined, so that efficient catalysis of aldol condensation reaction of methyl acetate and formaldehyde is realized. The invention provides a novel low-cost catalyst for green synthesis of methyl acrylate and a preparation method of the novel low-cost catalyst, and the novel low-cost catalyst has application potential in the field of catalytic chemistry.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a molecular sieve catalyst for synthesizing methyl acrylate through aldol condensation reaction of methyl acetate and formaldehyde, and belongs to the field of catalyst preparation. Background Art

[0002] Methyl acrylate (MA), as a key raw material in the field of organic chemicals and synthetic resins, occupies a pivotal position in many industries such as adhesives, coatings and super absorbent resins. However, the traditional acetone cyanohydrin method for producing MA has been criticized for environmental and safety issues due to the involvement of hazardous chemicals such as hydrocyanic acid. This challenge has prompted researchers to actively seek more efficient and environmentally friendly alternative processes. Among the many alternative technologies, the two-step synthesis of MA using propylene as raw material has made some progress, but its production stability is limited by fluctuations in raw material prices. Therefore, the research focus has shifted to the one-step aldol condensation reaction, that is, directly using formaldehyde and methyl acetate to synthesize methyl acrylate. This innovative process not only simplifies the production process, but also heralds cost reduction and improved environmental benefits.

[0003] The aldol condensation reaction of formaldehyde and acetic acid / ester is a typical acid-base catalytic reaction, and the properties of the catalyst are the key factors affecting the reaction performance. Patent CN101829558A discloses a catalyst for the direct synthesis of MMA from methyl propionate and formaldehyde and its preparation method. By introducing a non-ionic surfactant as a dispersion promoter during the Cs impregnation process, the dispersibility of the Cs species on the carrier surface is significantly improved, thereby improving the catalytic efficiency of the catalyst. Patent CN112371100B describes a metal Cs-modified B2O3 catalyst and its preparation method. The catalyst uses boric acid and polyvinyl pyrrolidone as modifiers. After impregnation and calcination with a SiO2 carrier, it exhibits excellent activity and stability in the catalytic acetic acid formaldehyde condensation reaction, and has lower preparation costs and higher activity, showing good industrial application potential. Patent CN109999922A introduces a new acid-base bifunctional catalyst with Cs as the active component, which is applied to the reaction of methyl propionate and formaldehyde to synthesize methyl methacrylate. This catalyst combines acidic and alkaline functions, and can catalyze complex reactions in the same catalyst system, greatly improving the efficiency and selectivity of the reaction. Patent CN104525176B provides a method for preparing Cs-based catalyst microspheres, which can significantly improve the catalytic efficiency and product yield of synthesizing methyl (meth)acrylate.

[0004] In the aldol condensation reaction, the selection and design of catalysts are crucial. Although alkali metal cesium is favored for its high efficiency, its high cost and scarcity limit its use in industrial applications. Therefore, the design and preparation of high-performance and low-cost catalysts that can replace the Cs active component has important research significance and application value. Summary of the invention

[0005] The present invention aims to provide a novel K / molecular sieve catalyst that can efficiently catalyze the aldol condensation reaction and a preparation method thereof. The core of the present invention is to prepare a catalyst that can efficiently catalyze the aldol condensation reaction of methyl acetate-formaldehyde by organically combining an alkali metal K active component with a molecular sieve of a specific topological structure, thereby effectively replacing conventional cesium-based catalysts and significantly reducing the preparation cost of the catalyst.

[0006] To achieve the above object, the present invention adopts the following technical solutions:

[0007] The metal-modified molecular sieve catalyst of the present invention is composed of two parts: one is alkali metal potassium as an active component, and the basic sites constructed on the surface of the carrier are crucial for the catalytic reaction; the other is a carrier that is a zeolite molecular sieve, selected from one or a mixture of MOR and FER zeolite molecular sieves. The loading amount of the alkali metal potassium active component needs to match the pores and acid properties of the carrier, accounting for 1-25wt% of the total mass of the catalyst, to ensure the best balance between catalytic efficiency and stability.

[0008] The preparation method of the catalyst comprises the following steps:

[0009] 1) Pretreatment of zeolite molecular sieve carrier: The selected molecular sieve carrier is subjected to high temperature calcination treatment, with the temperature controlled at 500-700°C for 2-8 hours. The purpose is to form suitable Lewis acid sites on the one hand, and to remove impurities and stabilize the carrier structure on the other hand.

[0010] 2) Carrier acid-base treatment: The pretreated carrier is treated with acid or / and alkali. The treatment liquid can be flexibly selected from concentrated nitric acid, citric acid, sodium hydroxide, ammonia water or tetrabutylammonium hydroxide, etc. The treatment conditions (temperature, time, liquid-to-solid ratio and concentration) are optimized to ensure the best effect. The treated carrier is further treated with ammonium

[0011] The treated H-type molecular sieve carrier is obtained by washing, drying, and re-calcining.

[0012] 3) Active metal loading: First, a salt solution containing potassium active components is prepared in a specific proportion, and the solution forms include acetate, nitrate, sulfate and chloride, etc. Subsequently, the prepared salt solution is fully mixed with the modified carrier by the equal volume impregnation method to ensure that the active components are evenly distributed on the surface of the carrier. After a certain period of standing (4-12 hours at 10-60°C), it is dried (6-12 hours at 100-120°C) and high-temperature calcined (2-12 hours at 400-600°C) to finally obtain a metal-modified molecular sieve catalyst loaded with active components. It is worth noting that in this step, the mass percentage of metal oxide in the molecular sieve is controlled at 1-25wt% to achieve the best balance of catalytic performance.

[0013] The potassium-modified zeolite molecular sieve catalyst is prepared through the above process, is suitable for the aldol condensation reaction of methyl acetate and formaldehyde, and is efficient in synthesizing methyl acrylate, showing excellent catalytic performance and application prospects.

[0014] The reaction conditions of the active metal-modified zeolite molecular sieve catalyst for the synthesis of methyl acrylate from methyl acetate and formaldehyde are: methyl acetate / formaldehyde is 1:1-8:1, methanol / formaldehyde is 1:1-5:1, and the feed space velocity is 0.5-3h -1 , the reaction temperature is 300℃-400℃.

[0015] In the aldol condensation reaction of methyl acetate and formaldehyde, a new type of molecular sieve catalyst with cheap alkali metal potassium as the active component and a specific microporous molecular sieve as the carrier significantly improved the reaction efficiency and product selectivity, and realized the replacement of alkali metal K for Cs. This reaction is essentially a process of acid-base synergistic catalysis. Specifically, the basic site is responsible for promoting the formation of carbon anions, which are then converted into enolate intermediates; while the acidic site is responsible for activating formaldehyde molecules to generate carbon cations. The two work synergistically to promote the aldol condensation reaction. By finely regulating the distribution of acid and base sites on the catalyst surface, the aldol condensation reaction is catalyzed with high activity and selectivity, thereby achieving the formation of the target product methyl acrylate.

[0016] Zeolite molecular sieves, as representatives of acidic carriers, are not only rich in medium-strong acid sites, but also provide abundant active sites for the interaction between metals and carriers with their huge specific surface area. In particular, the silanol groups in the molecular sieves can interact with the alkali metal K during the impregnation process to form Si-OK active species and new alkaline sites, which not only enhance the catalytic activity but also promote the uniform dispersion of metals. At the same time, the unique pore structure of zeolite molecular sieves helps promote the activation of substrate molecules and product selectivity, and improves the catalyst reaction activity and target product selectivity. BRIEF DESCRIPTION OF THE DRAWINGS DETAILED DESCRIPTION

[0017] The present invention is described in detail below by specific examples, but it should be understood that this is only an example and does not limit the scope of the present invention. Without departing from the technical core of the present invention, any replacement and change based on common technical knowledge and customary means all belong to the protection scope of the present invention. The molecular sieve used below was purchased from Nankai Catalyst Factory.

[0018] Embodiment 1:

[0019] Untreated hydrogen-type MOR molecular sieve with a silicon-aluminum atomic ratio of 15 (denoted as MOR-15), hydrogen-type MOR molecular sieve with a silicon-aluminum atomic ratio of 23 (denoted as MOR-23), hydrogen-type FER molecular sieve with a silicon-aluminum atomic ratio of 20 (denoted as FER-20), and hydrogen-type FER molecular sieve with a silicon-aluminum atomic ratio of 35 (denoted as FER-35) were directly used as comparison catalysts for reaction.

[0020] Catalyst test: The performance evaluation of the catalyst was carried out in a fixed bed reactor. The inner diameter of the reaction tube was 12 mm, the catalyst loading was 2.5 g, the raw material flow rate was 1 ml / h, and the raw materials included methyl acetate, trioxymethylene, and methanol, and their molar ratio was 2 / 1 / 2. The reactor temperature was 360 ° C and operated at normal pressure. After 3 hours of stable operation, the liquid products and tail gas were sampled and analyzed every 1 hour. The experimental repeatability and stability were good, and the quality difference before and after the reaction was within 5%. The liquid products were analyzed by FID gas chromatography, and the gas products were analyzed by TCD gas chromatography. The evaluation results are shown in Table 1.

[0021] Embodiment 2:

[0022] A hydrogen-type MOR molecular sieve with a silicon-aluminum atomic ratio of 15 was selected as a carrier, and the carrier was calcined at 600°C for 4 hours to obtain a calcined carrier; 1.06 g of potassium nitrate was dissolved in 6 ml of deionized water to prepare an impregnation solution, and the calcined zeolite molecular sieve carrier was placed in the impregnation solution, allowed to stand at room temperature for 12 hours, and then dried at 120°C for 12 hours to obtain a catalyst precursor; the obtained catalyst precursor was calcined at 500°C for 4 hours to obtain the target catalyst, recorded as Cat-1.

[0023] The obtained catalyst was tested for reaction performance in a fixed bed microreactor, with an inner diameter of 12 mm, a loading of 2.5 g, a raw material flow rate of 3 ml / h, a molar ratio of methyl acetate: formaldehyde: methanol = 2:1:2, a reaction temperature of 350°C, and normal pressure. After 3 hours of stable operation, samples were taken every hour for analysis. The experimental results were stable, with a mass difference of <5%. The liquid product was analyzed by FID, and the gas product was analyzed by TCD. See Table 1 for details.

[0024] Embodiment 3:

[0025] A hydrogen-type MOR molecular sieve with a silicon-aluminum atomic ratio of 23 was selected as a carrier, and the carrier was calcined at 600°C for 4 hours to obtain a calcined carrier; 1.06 g of potassium nitrate was dissolved in 6 ml of deionized water to prepare an impregnation solution, and the calcined zeolite molecular sieve carrier was placed in the impregnation solution, allowed to stand at room temperature for 12 hours, and then dried at 120°C for 12 hours to obtain a catalyst precursor; the obtained catalyst precursor was calcined at 500°C for 4 hours to obtain the target catalyst, recorded as Cat-2.

[0026] The obtained catalyst was tested for reaction performance in a fixed bed microreactor, with an inner diameter of 12 mm, a loading of 2.5 g, a raw material flow rate of 3 ml / h, a molar ratio of methyl acetate: formaldehyde: methanol = 2:1:2, a reaction temperature of 350°C, and normal pressure. After 3 hours of stable operation, samples were taken every hour for analysis. The experimental results were stable, with a mass difference of <5%. The liquid product was analyzed by FID, and the gas product was analyzed by TCD. See Table 1 for details.

[0027] Embodiment 4:

[0028] A hydrogen-type FER molecular sieve with a silicon-aluminum atomic ratio of 20 was selected as a carrier, and the carrier was calcined at 600°C for 4 hours to obtain a calcined carrier; 1.06 g of potassium nitrate was dissolved in 6 ml of deionized water to prepare an impregnation solution, and the calcined zeolite molecular sieve carrier was placed in the impregnation solution, allowed to stand at room temperature for 12 hours, and then dried at 120°C for 12 hours to obtain a catalyst precursor; the obtained catalyst precursor was calcined at 500°C for 4 hours to obtain the target catalyst, recorded as Cat-3.

[0029] The obtained catalyst was tested for reaction performance in a fixed bed microreactor, with an inner diameter of 12 mm, a loading of 2.5 g, a raw material flow rate of 3 ml / h, a molar ratio of methyl acetate: formaldehyde: methanol = 2:1:2, a reaction temperature of 350°C, and normal pressure. After 3 hours of stable operation, samples were taken every hour for analysis. The experimental results were stable, with a mass difference of <5%. The liquid product was analyzed by FID, and the gas product was analyzed by TCD. See Table 1 for details.

[0030] Embodiment 5:

[0031] A hydrogen-type FER molecular sieve with a silicon-aluminum atomic ratio of 35 was selected as a carrier, and the carrier was calcined at 600°C for 4 hours to obtain a calcined carrier; 1.06 g of potassium nitrate was dissolved in 6 ml of deionized water to prepare an impregnation solution, and the calcined zeolite molecular sieve carrier was placed in the impregnation solution, allowed to stand at room temperature for 12 hours, and then dried at 120°C for 12 hours to obtain a catalyst precursor; the obtained catalyst precursor was calcined at 500°C for 4 hours to obtain the target catalyst, recorded as Cat-4.

[0032] The obtained catalyst was tested for reaction performance in a fixed bed microreactor, with an inner diameter of 12 mm, a loading of 2.5 g, a raw material flow rate of 3 ml / h, a molar ratio of methyl acetate: formaldehyde: methanol = 2:1:2, a reaction temperature of 350°C, and normal pressure. After 3 hours of stable operation, samples were taken every hour for analysis. The experimental results were stable, with a mass difference of <5%. The liquid product was analyzed by FID, and the gas product was analyzed by TCD. See Table 1 for details.

[0033] Embodiment 6:

[0034] A hydrogen-type MOR molecular sieve with a silicon-aluminum atomic ratio of 15 was selected as a carrier, and the carrier was calcined at 600°C for 4 hours to obtain a calcined carrier; 0.92 g of potassium carbonate was dissolved in 6 ml of deionized water to prepare an impregnation solution, and the calcined zeolite molecular sieve carrier was placed in the impregnation solution, allowed to stand at room temperature for 12 hours, and then dried at 120°C for 12 hours to obtain a catalyst precursor; the obtained catalyst precursor was calcined at 500°C for 4 hours to obtain the target catalyst, recorded as Cat-5.

[0035] The obtained catalyst was tested for reaction performance in a fixed bed microreactor, with an inner diameter of 12 mm, a loading of 2.5 g, a raw material flow rate of 3 ml / h, a molar ratio of methyl acetate: formaldehyde: methanol = 2:1:2, a reaction temperature of 350°C, and normal pressure. After 3 hours of stable operation, samples were taken every hour for analysis. The experimental results were stable, with a mass difference of <5%. The liquid product was analyzed by FID, and the gas product was analyzed by TCD. See Table 1 for details.

[0036] Embodiment 7:

[0037] A hydrogen-type FER molecular sieve with a silicon-aluminum atomic ratio of 35 was selected as a carrier, and the carrier was calcined at 600°C for 4 hours to obtain a calcined carrier; 0.92 g of potassium carbonate was dissolved in 6 ml of deionized water to prepare an impregnation solution, and the calcined zeolite molecular sieve carrier was placed in the impregnation solution, allowed to stand at room temperature for 12 hours, and then dried at 120°C for 12 hours to obtain a catalyst precursor; the obtained catalyst precursor was calcined at 500°C for 4 hours to obtain the target catalyst, recorded as Cat-6.

[0038] The obtained catalyst was tested for reaction performance in a fixed bed microreactor, with an inner diameter of 12 mm, a loading of 2.5 g, a raw material flow rate of 3 ml / h, a molar ratio of methyl acetate: formaldehyde: methanol = 2:1:2, a reaction temperature of 350°C, and normal pressure. After 3 hours of stable operation, samples were taken every hour for analysis. The experimental results were stable, with a mass difference of <5%. The liquid product was analyzed by FID, and the gas product was analyzed by TCD. See Table 1 for details.

[0039] Embodiment 8:

[0040] A hydrogen-type MOR molecular sieve with a silicon-aluminum atomic ratio of 23 was selected as a carrier, and the carrier was calcined at 600°C for 4 hours to obtain a calcined carrier; 0.53 g of potassium nitrate was dissolved in 6 ml of deionized water to prepare an impregnation solution, and the obtained calcined zeolite molecular sieve carrier was placed in the impregnation solution, allowed to stand at room temperature for 12 hours, and then dried at 120°C for 12 hours to obtain a catalyst precursor; the obtained catalyst precursor was calcined at 500°C for 4 hours to obtain the target catalyst, recorded as Cat-7.

[0041] The obtained catalyst was tested for reaction performance in a fixed bed microreactor, with an inner diameter of 12 mm, a loading of 2.5 g, a raw material flow rate of 2 ml / h, a molar ratio of methyl acetate: formaldehyde: methanol = 2:1:2, a reaction temperature of 360°C, and normal pressure. After 3 hours of stable operation, samples were taken every hour for analysis. The experimental results were stable, with a quality difference of <5%. The liquid product was analyzed by FID, and the gas product was analyzed by TCD. See Table 1 for details.

[0042] Embodiment 9:

[0043] A hydrogen-type MOR molecular sieve with a silicon-aluminum atomic ratio of 23 was selected as a carrier, and the carrier was calcined at 600°C for 4 hours to obtain a calcined carrier; 0.78 g of potassium carbonate was dissolved in 6 ml of deionized water to prepare an impregnation solution, and the calcined zeolite molecular sieve carrier was placed in the impregnation solution, allowed to stand at room temperature for 12 hours, and then dried at 120°C for 12 hours to obtain a catalyst precursor; the obtained catalyst precursor was calcined at 500°C for 4 hours to obtain the target catalyst, recorded as Cat-8.

[0044] The obtained catalyst was tested for reaction performance in a fixed bed microreactor, with an inner diameter of 12 mm, a loading of 2.5 g, a raw material flow rate of 3 ml / h, a molar ratio of methyl acetate: formaldehyde: methanol = 2:1:2, a reaction temperature of 360°C, and normal pressure. After 3 hours of stable operation, samples were taken every hour for analysis. The experimental results were stable, with a quality difference of <5%. The liquid product was analyzed by FID, and the gas product was analyzed by TCD. See Table 1 for details.

[0045] Embodiment 10:

[0046] A hydrogen-type FER molecular sieve with a silicon-aluminum atomic ratio of 60 was selected as a carrier, and the carrier was calcined at 500°C for 8 hours to obtain a calcined carrier; 1.7 g of potassium oxalate was dissolved in 6 ml of deionized water to prepare an impregnation solution, and the calcined zeolite molecular sieve carrier was placed in the impregnation solution, allowed to stand at room temperature for 12 hours, and then dried at 120°C for 12 hours to obtain a catalyst precursor; the obtained catalyst precursor was calcined at 400°C for 8 hours to obtain the target catalyst, recorded as Cat-9.

[0047] The obtained catalyst was tested for reaction performance in a fixed bed microreactor, with an inner diameter of 12 mm, a loading of 2.5 g, a raw material flow rate of 3 ml / h, a molar ratio of methyl acetate: formaldehyde: methanol = 2:1:2, a reaction temperature of 360°C, and normal pressure. After 3 hours of stable operation, samples were taken every hour for analysis. The experimental results were stable, with a quality difference of <5%. The liquid product was analyzed by FID, and the gas product was analyzed by TCD. See Table 1 for details.

[0048] Embodiment 11:

[0049] A hydrogen-type FER molecular sieve with a silicon-aluminum atomic ratio of 60 was selected as a carrier, and the carrier was calcined at 500°C for 8h to obtain a calcined carrier; 100ml of a 0.1mol / L sodium hydroxide aqueous solution was weighed and added to a round-bottom flask, and 5g of the pretreated MOR carrier was weighed and added to the round-bottom flask, and the treatment time was 12h at a temperature of 60°C. After the treatment, it was filtered, washed with deionized water, dried at 100°C for 4h, and finally calcined at 500°C for 5h to obtain a carrier treated with sodium hydroxide. The treated carrier was further treated with ammonium exchange and calcined to obtain an H-type sample. 1.7g of potassium oxalate was dissolved in 6ml of deionized water to prepare an impregnation solution, and the treated hydrogen-type zeolite molecular sieve carrier was placed in the impregnation solution, left to stand at room temperature for 12h, and then dried at 120°C for 12h to obtain a catalyst precursor; the obtained catalyst precursor was calcined at 400°C for 8h to obtain the target catalyst, which was recorded as Cat-10.

[0050] The obtained catalyst was tested for reaction performance in a fixed bed microreactor, with an inner diameter of 12 mm, a loading of 2.5 g, a raw material flow rate of 3 ml / h, a molar ratio of methyl acetate: formaldehyde: methanol = 2:1:2, a reaction temperature of 360°C, and normal pressure. After 3 hours of stable operation, samples were taken every hour for analysis. The experimental results were stable, with a quality difference of <5%. The liquid product was analyzed by FID, and the gas product was analyzed by TCD. See Table 1 for details.

[0051] Comparative Example 1:

[0052] The impregnation solution was changed to sodium nitrate solution, and the other steps of catalyst preparation and catalyst reaction evaluation were the same as in Example 2, and the catalyst was recorded as Na / MOR-15. The reaction results are shown in Table 2.

[0053] Comparative Example 2:

[0054] The impregnation solution was changed to lithium nitrate solution, and the other steps of catalyst preparation and catalyst reaction evaluation were the same as those in Example 2, and the catalyst was recorded as Na / MOR-15. The reaction results are shown in Table 2.

[0055] Comparative Example 3:

[0056] The carrier was changed to silicon oxide, and the other steps of catalyst preparation and catalyst reaction evaluation were the same as in Example 2, and the catalyst was recorded as K / SiO2. The reaction results are shown in Table 2.

[0057] Table 1:

[0058] Catalyst No. Methyl acetate conversion rate / % Methyl acrylate selectivity / % MOR-15 12 29 MOR-23 7 23 FER-20 21 46 FER-35 13 37 Cat 1 39 86 Cat 2 42 91 Cat 3 29 88 Cat 4 31 85 Cat 5 32 84 Cat 6 28 77 Cat 7 52 82 Cat 8 33 93 Cat 9 39 86 Cat 10 45 94

[0059] Table 2:

[0060]

[0061]

Claims

1. A K / molecular sieve type catalyst for synthesizing methyl acrylate from methyl acetate and formaldehyde, characterized in that: The active component of the catalyst is alkali metal potassium, and the carrier is selected from one or two of FER and MOR type zeolite molecular sieves.

2. The K / molecular sieve type catalyst according to claim 1, characterized in that: The K active component is selected from one or two of potassium chloride, potassium sulfate, potassium nitrate, potassium carbonate or potassium hydroxide.

3. The catalyst for K / molecular sieve type according to claim 1, characterized in that: The loading amount of the active component is 1-25 wt% of the total mass of the catalyst, based on the carrier and calculated as the active component oxide.

4. The catalyst for synthesizing methyl acrylate from methyl acetate and formaldehyde according to claim 1, characterized in that: The preparation method of the catalyst comprises the following steps: (1) calcining the molecular sieve carrier at 500-700°C for 2-8h; (2) placing the zeolite molecular sieve carrier obtained in (1) in an impregnation solution containing active components, standing at 10-60° C. for 4-12 hours, and drying at 100-120° C. for 6-12 hours to obtain a catalyst precursor; (3) The catalyst precursor obtained in (2) is calcined at 400-600° C. for 2-12 h to obtain the target catalyst.

5. The K / molecular sieve type catalyst according to claim 1, characterized in that: The zeolite molecular sieve carrier is selected from one or two of MOR or FER type zeolite molecular sieves, and the silicon-aluminum atomic ratio is 10-100; the zeolite molecular sieve carrier is H type; the zeolite molecular sieve carrier can be treated by one or more methods of inorganic acid, organic acid, inorganic base and organic base.

6. The use of a zeolite molecular sieve carrier catalyst for aldol condensation according to claim 1, characterized in that: Used for preparing methyl acrylate from formaldehyde and methyl acetate, the aldol condensation catalyst is loaded in a fixed bed reaction tube, the reaction temperature is 300-400°C, the reaction pressure is normal pressure, a mixed liquid of methyl acetate, methanol and formaldehyde source in a certain molar ratio is passed into the fixed bed, wherein the formaldehyde source is trioxymethylene, methyl acetate / formaldehyde is 1:1-8:1, methanol / formaldehyde is 1:1-5:1, and the liquid hourly space velocity of the feed is 0.5-3h -1 .

Citation Information

Patent Citations

  • Catalyst for directly preparing methyl methacrylate by reacting methyl propionate with formaldehyde and preparation method thereof

    CN101829558A

  • Preparation method of Cs-based catalyst microspheres, microspheres prepared therefrom, and method for synthesizing methyl methacrylate using the microspheres.

    CN104525176B

  • Acid-base bifunctional catalyst for synthesis of methyl methacrylate by methyl propionate and formaldehyde

    CN109999922A

  • A metal Cs-modified B2O3 catalyst, its preparation method and application

    CN112371100B

  • Catalyst containing metal modified molecular sieve with FER configuration and preparation method of catalyst

    CN108097296A